Microcontroller Based Money Storing Tools with Web Monitoring and Social Media - Prayoga Aldi Kurniawan; Ritzkal Ritzkal; Bayu Adhi Prakosa (Jurnal Mantik, 2021)
The money deposit box is one of the equipment at home that functions as a place to store money, although there are many practical money storage media, but there are still those who like to store money in the Money Deposit Box but in that storage many do not know how much the nominal money is. already saved. For this reason, a money storage box based on the Arduino Mega microcontroller was made. This tool can provide information on the amount of money saved and is equipped with a lock as a security. This study designs the hardware platform: (1) Ardunio Mega 2560 (2) TCS3200 sensor (3) DC motor (4) LCD i2C (5) 1ch relay (6) selenoyd doorlock (7) RTC DS3231 (8) Ethernet shield module, and Software: (1)Windows 10 (2)Arduino IDE 1.8 (2)XAMPP 3.2 (3)PHP 10 (4)MySQL (5)Visual Studio Code 1.5 The system is connected to the Internet Network. the data flow will be stored into a MySQL-based database at the NCC Lab, the nominal money obtained from reading the TCS3200 will be flowed through the Internet network, where the use of the ethernet shield module can integrate money storage equipment on the computer with a local MySQL database. Integration of hardware components, software and internet network.